Pedra, cal e pessoas: as memórias e transformações na rua da Areia em João Pessoa – PB - Carneiro, Natália Vieira (2022)
This research aims at the debate about Rua da Areia, former urban artery, located in the central area of the City of João Pessoa, between the neighborhoods of Centro and Varadouro, discussing its relations with the city around the existing and experienced dynamics of the old urban network. Thus, the objective of the research was to cover the real and contemporary situation of Rua da Areia, understanding it in the whole process of urbanization of the city of João Pessoa and its processof (des) patrimonialization bringing the idea of preservation of a landscape coming with a singular architecture and great value for the community, as well as the experiences linked to them. Moreover, the theme is justified in order to propose the valorization of local history, through its process of identity and social memory present in the dailylife of the various social groups of the area, understanding how they sustain and change, through power relations and sociability present in the Street. The work also permeates the importance of approaching heritage education as a practice of the exercises of the look from the experience and visits in the field linked to cultural heritage and its affective experiences. It is essential to approach that the dissertation is inserted in the concentration area "History and Historical Culture" of the Postgraduate Program in History at the Federal University of Paraíba, in the research line "Teaching History and Historical Knowledge", includin gits formal transformations, a study that takes into account the circulation of the forms led by the population and their memories tied to the context of the research. Thus, it was possible to observe that the unveiling and complexity of the process of (des) patrimonialization of Rua da Areia, linked to territorial disputes and dissent, presented a multiplicity of agents and senses, that is, this ancient artery of the city of João Pessoa showed us na urban dynamics and a diversity of social actor sinter connected to the built heritage, who are in a state of degradation, having their prostheses as a form of resistance to the transformations experienced. Thus, a study of the environment was proposed, in order to contribute to the strength ening and dissemination of pessoense cultural heritage through feelings of belonging and collective memory.